Topical Timolol Vs. Oral Propranolol for the Treatment of Superficial Infantile Hemangiomas - Wu, Hai Wei; Wang, Xuan; Zhang, Ling; Zheng, Jia Wei; Liu, Chao; Wang, Yan An (Frontiers in Oncology, 2018)
Objective:Infantile hemangiomas (IHs) are the most common vascular tumors of infancy. Oral propranolol has achieved a great success in treating IHs since 2008. To minimize the systemic side events caused by oral administration of propranolol, topical timolol started to be applied in the treatment of IHs, especially for superficial lesions. Methods: We treated 724 children with superficial IHs using oral propranolol or topical timolol, and investigated the efficacy and safety of the two treatment patterns. Results: Both oral propranolol and topical timolol achieved a satisfactory therapeutic outcome, with a effective response rate of 97% and 96.4%. No significant differences in visual analogue scale (VAS) improvement between two groups were observed in the present study. Occurrence rate of systemic adverse events for patients treated with oral propranolol (3.9%) was much higher than that for patients treated with topical timolol (0%). Clinical response was not associated with gender, duration of treatment, lesion location, gestational age and progesterone use during pregnancy, but closely associated with age at treatment initiation. Conclusions: We recommend that topical timolol instead of oral propranolol should be the first-line therapy for superficial IHs because of its good efficacy and improved safety.